2013
DOI: 10.3922/j.psns.2013.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Temporal control in chained fixed-ratio, fixed-interval schedules.

Abstract: Four rats were subjected to chained fixed-ratio (FR), fixed-interval (FI) schedules of reinforcement (chain FR 5 FI). A FR schedule at one lever produced a discriminative stimulus (i.e., light) associated with an FI schedule of primary reinforcement (water) at the second response lever. The FR schedule was kept constant, whereas the FI length was changed from 10 to 60 s under five different experimental conditions. Increases in the FI length resulted in increases in pre-ratio pauses, but pauses in the FI tende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Think of pausing as the initial IRT and compare with Equation 11. Todorov and associates (Todorov et al, 2013) found that pausing in the first link of a chained FR‐FI schedule was a linear function of the length of the second component. Neuringer (1969) measured response rates in the initial links of concurrent‐chained VI‐FI schedules.…”
Section: Linearization Of the Functionsmentioning
confidence: 99%
“…Think of pausing as the initial IRT and compare with Equation 11. Todorov and associates (Todorov et al, 2013) found that pausing in the first link of a chained FR‐FI schedule was a linear function of the length of the second component. Neuringer (1969) measured response rates in the initial links of concurrent‐chained VI‐FI schedules.…”
Section: Linearization Of the Functionsmentioning
confidence: 99%